2022
DOI: 10.1002/adfm.202207259
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Long‐Wavelength Emissive Organic Nanosonosensitizer Targeting Mitochondria for Precise and Efficient In Vivo Sonotherapy

Abstract: As a modern biomedical therapeutic modality, sonodynamic therapy (SDT) presents unique advantages, including superior tissue penetration capability, temporal-spatial controllability, and negligible side effects. However, the bottlenecks of most organic sonosensitizers are their short emission wavelengths, strong phototoxicity, and unsatisfactory SDT effect, which undermines the precise fluorescence imaging-guided SDT in vivo. Here, a long-wavelength emissive and mitochondria-targeted organic nanosonosensitizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…[29] To fabricate the CF-loaded folate-targeted nano probes (FA-CF-NPs), the nano-coprecipitation method was performed (Figure 1a). [30,31] Then, a series of experiments were carried out to characterize the morphology, size, and optical properties of the obtained FA-CF-NPs. Transmission electron microscopy (TEM) imaging showed that the prepared FA-CF-NPs were spherical with an average diameter of 7.2 ± 1.3 nm (Figure 1b).…”
Section: Characterization Of Fa-cf-npsmentioning
confidence: 99%
“…[29] To fabricate the CF-loaded folate-targeted nano probes (FA-CF-NPs), the nano-coprecipitation method was performed (Figure 1a). [30,31] Then, a series of experiments were carried out to characterize the morphology, size, and optical properties of the obtained FA-CF-NPs. Transmission electron microscopy (TEM) imaging showed that the prepared FA-CF-NPs were spherical with an average diameter of 7.2 ± 1.3 nm (Figure 1b).…”
Section: Characterization Of Fa-cf-npsmentioning
confidence: 99%
“…Following this work, NIR-II fluorescence imaging technology emerged and has been used in the biomedical field and other scientific research areas. 39…”
Section: Application Of Metallacycles/metallacages In Tumor Imaging A...mentioning
confidence: 99%
“…Among them, SDT, that produces ROS through sonosensitizers under US irradiation leading to cancer cell oxidative stress, necrosis, and apoptosis, has drawn much more attention due to its deep tissue penetration depth and non-invasiveness. As the key of SDT, various sonosensitizers have been explored in recent years, including organic and inorganic sonosensitizers. The commonly used organic sonosensitizers inevitably exhibited phototoxicity and low biological stability, along with short circulation time. Although inorganic sonosensitizers can overcome these shortcomings, such as MOFs, noble metal nanoparticles, metallic oxide, carbon structures derived from MOFs, black phosphorus, etc., their nonbiodegradability and potential long-term side effects are still the main obstacles to limit their further application.…”
Section: Introductionmentioning
confidence: 99%